Programmable logic controller-based automatic control for municipal wastewater treatment plant optimization. Issue 1 (9th December 2021) - Ning, Shunli; Hong, Siyuan
Abstract: The treatment of industrial wastewater can effectively protect the water environment and maintain sustainable development. This paper introduces an incremental proportion and integration (IPI) control algorithm-based programmable logic controller (PLC) used to adjust the aeration tank's dissolved oxygen content automatically in the wastewater treatment process. The control algorithm was improved by a back-propagation neural network (BP-NN). An instance analysis was carried out on a wastewater treatment plant in Zhejiang Province, China. This showed that the BP-NN improved control algorithm made the aeration tank's dissolved oxygen content more stable at the set value than it was with manual adjustment and the conventional algorithm. The total nitrogen content in wastewater treated in the aeration tank under the control of the improved IPI algorithm was minimized and fluctuated least. The aeration tank blower's power consumption was also at its lowest under the control of the improved IPI algorithm. HIGHLIGHTS: The wastewater was treated by the activated sludge method. The content of dissolved oxygen in the wastewater collected by a detector was taken as the basis of automatic control. PI parameters were adaptively adjusted using BP network. The wastewater treatment effect was measured by the total nitrogen content in the wastewater. The air blower was used to provide dissolved oxygen for wastewater and play a role of stirring.